Electrical characteristics of collective 0+ and 2+ states in 158,160Gd isotopes - Usmanov, Fhazlitdin; Okhunov, Abdurahim; Abu Kassim, Hasan; Yusupov, E'lmurod; Salikhbaev, Umar (2018)
The theoretical analysis ofelectric characterisfics ofthe positive parity states in isotopes 158,160Gd been carried out in the phenomenological model taking into account Coriolis mixing of low–lying sates in rotational bands The energy spectrum of the levels states and the reduced probabilities of E2– transitions have been calculated. The calculated values of ration of E2– transition probabilities from the (beta_1), (beta_2), (gamma) and bands are compared with the available experimental data which are in best agreement. It is shown that the effect of mixing of the low-lying bands plays an important role and it is significantly shown in probabilities of electric transitions even at low spins.